Transcriptional responses of three model diatoms to nitrate limitation of growth - Bender, Sara J.; Durkin, Colleen A.; Berthiaume, Chris T.; Morales, Rhonda L.; Armbrust, E. Virginia (Frontiers in Marine Science, 2014)
Diatoms are among the most diverse groups of phytoplankton in the ocean. Despite their widely recognized influence on ocean ecosystems and global biogeochemistry, little is known about the impact of this diversity on large-scale processes. Here, we examined the ramifications of between-species diversity by documenting the transcriptional response of three diatoms - Thalassiosira pseudonana, Fragilariopsis cylindrus, and Pseudo-nitzschia multiseries - to the onset of nitrate limitation of growth, a common limiting nutrient in the ocean. The three species shared 5,583 clusters of orthologous genes based on OrthoMCL clustering of publically available diatom genomes. These clusters represent 30-54% of the predicted genes in each diatom genome. Less than 5% of genes within these core clusters displayed the same transcriptional responses across species when growth was limited by nitrate availability. Orthologs, such as those involved in nitrogen uptake and assimilation, as well as carbon metabolism, were differently expressed across the three species. The two pennate diatoms, F. cylindrus and P. multiseries, shared 3,839 clusters without orthologs in the genome of the centric diatom T. pseudonana. A majority of these pennate-clustered genes, as well as the non-orthologous genes in each species, had minimal annotation information, but were often significantly differentially expressed under nitrate limitation, indicating their potential importance in the response to nitrogen availability. Despite these variations in the specific transcriptional response of each diatom, overall transcriptional patterns suggested that all three diatoms displayed a common physiological response to nitrate limitation that consisted of a general reduction in carbon fixation and carbohydrate and fatty acid metabolism and an increase in nitrogen recycling. Characterization of these finely tuned responses will help to better predict which types of diatoms will bloom under which sets of environmenta